Convergence of the branching Bellman— Harrison Processes - Aliev, S. A. (Ukrains’kyi Matematychnyi Zhurnal, 1990)
A limit theorem regarding the convergence of a sequence of normalized Bellman — Harris processes to an Jirina process (a branching process with a continuous phase space) is obtained.